Pengaruh Budaya Organisasi Dan Motivasi Terhadap Kinerja Tenaga Pendidik - Gurawan Dayona; Luska Lusyana Sari; Riyandi Nur Sumawidjaja; Yoyo Sudaryo (Transformasi Manageria: Journal of Islamic Education Management, 2023)
The purpose of this study was to determine the effect of organizational culture and motivation on the performance of teaching staff at MedikaCom Vocational High School. This research uses descriptive verification method. Data was collected through a survey of all teaching staff at the MedikaCom Vocational High School. The data is processed using a statistical application with the method of path analysis (path analysis). The results showed that the conditions of organizational culture, motivation and performance of teaching staff were in the Good category. This study also shows that there is a strong correlation between organizational culture, motivation, and performance. Processed data confirms that organizational culture and motivation have a positive and significant effect on performance. The influence of organizational culture and motivation on the performance of teaching staff at Medikacom Vocational High School can be seen from the value of the coefficient of determination (R2) or R Square of 0.789. These results indicate that the simultaneous contribution of organizational culture and motivation to performance is 78.9%. While the remaining 21.1% is the influence of other variables (epsilon) that were not examined by the authors.